Place Attachment towards Shopping Districts in Kuala Lumpur City Centre, Malaysia - Ujang, Norsidah (2008)
One of the urban design issues concerning Kuala Lumpur is the weakening of the city identity. Changes in the city’s physical environment and the subsequent shift in the users’ perception will continue to be translated into interventions that proved to have altered the urban fabric and disrupted its sense of place. Concurrently, place meanings and attachment are diminishing. In urban design research, much has been discussed on the significance of the physical elements and activities in creating the sense of place and identity; however the role of place attachment as a component of place that gives meaning(s) has not been adequately explored. The aim of the research is to examine place attachment of users from selected places within the city centre of Kuala Lumpur and its associated meanings and influencing factors. The research adopted a mixed methodological approach and strategy in data collection and analysis. Surveys and face-to-face interviews were conducted with users of three selected shopping districts comprising four main shopping streets of Kuala Lumpur to elicit relevant data. The streets are Jalan Tunku Abdul Rahman (JTAR) together with Jalan Masjid India (JMI), Jalan Petaling (JP) and Jalan Bukit Bintang (JBB). A total of 330 randomly selected respondents participated in the survey and 36 purposely chosen respondents were interviewed in the locations. Systematic field observation was carried out to gather evidence of the actual scenes of the places. Urban character appraisal was done to determine the capacity of the places to support users’ activities based on performance indicators established by the researcher. Multiple sources of evidence are gathered, analysed and triangulated and the findings of the research were derived from the convergence of the data. The research has found that place attachment influences the users’ perception of the shopping streets. The places were not only identified based on the quality of the physical elements and diversity of human activities but also based on the attachment and meanings associated with the experience of the places. The form and degree of attachment to the places were influenced by the level of familiarity, the length of engagement, the degree of economic dependency, the role of the users and the ethnic background. The research has established that in securing local place identity, place attachment is one of the factors that should be considered in the design of urban places in Malaysia.